Examining the viability of the world’s busiest winter road to climate change using a process-based lake model - Mullan, DJ; Barr, ID; Flood, RP; Galloway, JM; Newton, AMW; Swindles, GT (American Meteorological Society, 2021)
Winter roads play a vital role in linking communities and building economies in the northern high latitudes. With these regions warming two to three times faster than the global average, climate change threatens the long-term viability of these important seasonal transport routes. We examine how climate change will impact the world’s busiest heavy-haul winter road – the Tibbitt to Contwoyto Winter Road (TCWR) in northern Canada. The FLake freshwater lake model is used to project ice thickness for a lake at the start of the TCWR – first using observational climate data, and second using modelled future climate scenarios corresponding to varying rates of warming ranging from 1.5°C to 4°C above preindustrial temperatures. Our results suggest that 2°C warming could be a tipping point for the viability of the TCWR, requiring at best costly adaptation and at worst alternative forms of transportation. Containing warming to the more ambitious temperature target of 1.5°C pledged at the 2016 Paris Agreement may be the only way to keep the TCWR viable – albeit with a shortened annual operational season relative to present. More widely, we show that higher regional winter warming across much of the rest of Arctic North America threatens the long-term viability of winter roads at a continental scale. This underlines the importance of continued global efforts to curb greenhouse gas emissions to avoid many long-term and irreversible impacts of climate change.